The ubiquitin proteasome system in Caenorhabditis elegans and its regulation - Nikoletta Papaevgeniou; Niki Chondrogianni (Redox Biology, 2014)
Protein degradation constitutes a major cellular function that is responsible for maintenance of the normal cellular physiology either through the degradation of normal proteins or through the elimination of damaged proteins. The Ubiquitin–Proteasome System (UPS)1 is one of the main proteolytic systems that orchestrate protein degradation. Given that up- and down- regulation of the UPS system has been shown to occur in various normal (such as ageing) and pathological (such as neurodegenerative diseases) processes, the exogenous modulation of the UPS function and activity holds promise of (a) developing new therapeutic interventions against various diseases and (b) establishing strategies to maintain cellular homeostasis. Since the proteasome genes are evolutionarily conserved, their role can be dissected in simple model organisms, such as the nematode, Caenorhabditis elegans. In this review, we survey findings on the redox regulation of the UPS in C. elegans showing that the nematode is an instrumental tool in the identification of major players in the UPS pathway. Moreover, we specifically discuss UPS-related genes that have been modulated in the nematode and in human cells and have resulted in similar effects thus further exhibiting the value of this model in the study of the UPS.